Study of vibration protection system of the operator’s seat under polyharmonic external influences - Korytov M.S.; Sherbakov V.S.; Kashapova I.E. (Научно-технический вестник Брянского государственного университета)
The problem of protection of operators of ground transportation and technological machines from vibrations is actual. A mathematical model with one translational degree of freedom is used for the vibration protection system of the operator’s seat. RMS values of vertical acceleration of the vibration-protected mass, i.e. the seat with the operator, should not exceed the limit values established by sanitary norms. Vibrations in the frequency range up to 40 Hz are the most dangerous. The values of parameters of external influences in the form of harmonic vibrations of the floor of the opera-tor’s cabin are established, at which the established limit values of RMS acceleration of the seat with the operator are observed. For this purpose the calculation scheme is developed and the parameters of harmonic influence on the base of the vibration protection system are allocated. Analytical expressions linking the acceleration and amplitude of absolute displacements of the vibration-protected mass with the acceleration and amplitude of harmonic forcing vibrations of the base, as well as the amplitude of the suspension stroke are obtained. Numerical summation of harmonic vibrations of the seat base causing limiting RMS accelerations at various frequencies up to 40 Hz, specified by sanitary norms, al-lowed to consider complex vibrations of the seat at polyharmonic vibrations of the base. At polyharmonic influences with the use of deduced analytical expressions, for the mass of the seat with the operator one hundred kilograms, the dependences of accelerations of the vibration-protected mass and the seat base on the structural parameters of the system, such as the stiffness coefficient and the viscous friction coefficient of the vibration-protecting mechanism were obtained. It was found that the rms value of absolute accelerations of the vibration-protected mass at complex displacements of the base remains approximately constant at different values of the stiffness coefficient and resistance coefficient of the system. At the same time, polyharmonic vibrations of the seat base, are characterized by a large scatter of the value of the RMS acceleration. The highest value of the RMS acceleration of the seat base is achieved at values of the stiffness coefficient and resistance coefficient of the system close to zero.